2018
DOI: 10.1590/s1679-45082018ao4189
|View full text |Cite
|
Sign up to set email alerts
|

The importance of dysphagia screening and nutritional assessment in hospitalized patients

Abstract: Objective:To determine frequency of dysphagia risk and associated factors in hospitalized patients as well as to evaluate nutritional status by using different methods and correlate the status with scores of the Eating Assessment Tool (EAT-10).Methods:This was a cross-sectional study including 909 inpatients of a philanthropic hospital. For the diagnosis of dysphagia we used an adapted and validated Brazilian version of the Eating Assessment Tool (EAT-10). The nutritional status was evaluated through the subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 25 publications
2
28
0
11
Order By: Relevance
“…Since it is well known that tongue pressure and masticatory function decrease with resection, especially in patients with oral cancer, our results also support the results of previous studies [20,21]. In addition, a cross-sectional study of 909 hospitalized patients showed an association between EAT-10 levels and nutritional status, and the results of this study were similar [22]. Therefore, malnutrition may occur due to type I postoperative oral dysfunction (transport type).…”
Section: Discussionsupporting
confidence: 91%
“…Since it is well known that tongue pressure and masticatory function decrease with resection, especially in patients with oral cancer, our results also support the results of previous studies [20,21]. In addition, a cross-sectional study of 909 hospitalized patients showed an association between EAT-10 levels and nutritional status, and the results of this study were similar [22]. Therefore, malnutrition may occur due to type I postoperative oral dysfunction (transport type).…”
Section: Discussionsupporting
confidence: 91%
“…In the same study, in addition to low BMI (<22 kg/m 2 ), insufficient oral intake, chewing problems, immobility, advanced age, and female gender were cited among the most significant risk factors for malnutrition 30. Andrade et al5 conducted a study of 909 hospitalized patients in Portugal and evaluated the risk of dysphagia with the EAT-10 scale and nutritional status with the SGA. The risk of dysphagia was determined to be 10.5% and that of malnutrition was reported as 13.2% 5.…”
Section: Discussionmentioning
confidence: 99%
“…Andrade et al5 conducted a study of 909 hospitalized patients in Portugal and evaluated the risk of dysphagia with the EAT-10 scale and nutritional status with the SGA. The risk of dysphagia was determined to be 10.5% and that of malnutrition was reported as 13.2% 5. The authors noted that the risk of dysphagia and malnutrition increased especially with age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also associated with reduced quality of life, social isolation, dehydration, malnutrition, and aspiration pneumonia 35 . The latter is one of the leading causes of death in PD 36 . Changes related to dysphagia have a direct influence on the nutritional status, since changes in food consistency and the difficulty of ingestion itself can hinder dietary adjustments 36 .…”
Section: Discussionmentioning
confidence: 99%